Pengaruh Kepercayaan Diri dan Motivasi Belajar terhadap Literasi Matematika Siswa Sekolah Dasar: Uji Regresi Linear Berganda - Amaliyah, Fitriyah (Journal Prakarsa Paedagogia, 2025)
Self-confidence and learning motivation are affective factors that are thought to contribute to elementary school students' mathematical literacy. Mathematical literacy is an important skill in learning such as AKM, but it is still low in this school. This study aims to examine the effect of self-confidence and learning motivation on the mathematical literacy of fourth-grade students at SDN 1 Rendeng Kudus. The research approach used is quantitative with a causal associative type and explanatory design. The sample consisted of 30 students with a saturated sample technique. The research instruments were Likert scale questionnaires and mathematical literacy tests based on AKM questions. Data analysis techniques included prerequisite tests and multiple linear regression analysis. The results of the F test showed a significance of 0.019 (0.05) which means there is a significant effect simultaneously. The t test showed a significance of 0.005 for self-confidence and 0.03 for learning motivation. The R² value of 0.200 indicates that both variables explain 20% of the variation in mathematical literacy. This finding confirms the importance of strengthening the affective aspect in mathematics learning in elementary schools.